2017
DOI: 10.1097/pq9.0000000000000033
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Asthma Medication Delivery Program: An Initiative to Provide Discharge Prescriptions and Education

Abstract: Background:Prescription fill rates for children being discharged from the emergency department (ED) after asthma exacerbations are low, placing the child at risk for additional ED visits or admissions for asthma. This article describes the implementation of an ED asthma prescription delivery service designed to improve pharmacy prescription capture and decrease ED revisit rates.Methods:A core group developed a service to provide asthma prescriptions and education to patients in their ED room before discharge. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses 12,21,22 . To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses 12,21,22 . To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many existing bedside medication delivery programs in the literature are standalone or targeted to specific populations, mainly based on readmission penalties via HRRP services and discharge diagnoses. 12,21,22 To our knowledge, this is the first study to examine whether reducing travel and financial barriers to obtaining medications reduces readmissions based on comorbidities and medical complexity, as well as primary disease diagnosis. We found that providing prescriptions and combining a subsidy to reduce financial burdens lowers readmissions compared with controls and simply providing medicines; focusing on patients with 0 or ≥ 4 comorbidities provided the greatest impact.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers in several studies have focused on discharge prescription programs for children with chronic diseases like asthma. 1,12,20 Hatoun et al 1 and Hiteshew et al 12 identified that filling asthma medications in the hospital outpatient pharmacy reduced 30-day ER visit and readmission rates, respectively. Given the multifactorial nature of readmissions and our low baseline readmission rate of ,2%, our study was not powered to detect a significant change in readmission rates.…”
Section: Discussionmentioning
confidence: 99%